Application of curcumin and its derivatives in tumor multidrug resistance. (7th April 2020) - Xu, Ting; Guo, Pu; He, Yingmeng; Pi, Chao; Wang, Yuanyuan; Feng, Xianhu; Hou, Yi; Jiang, Qingsheng; Zhao, Ling; Wei, Yumeng
Abstract: Malignant tumor endangers seriously the health of all mankind. Multidrug resistance (MDR) is one of the main causes of clinical tumor chemotherapy failure. Curcumin (CUR) has not only antitumor activity but also reversing tumor MDR effect. CUR reverses tumor MDR via regulating related signal pathways or corresponding expressed proteins or gene. When combined with chemotherapeutic agents, CUR can be a chemotherapeutic sensitive agent to enhance chemotherapy efficacy and weaken tumor MDR. On the other hand, to improve the MDR reversal effect of CUR, its derivatives have been extensively studied. Therefore, this article mainly focuses on reviewing the application of CUR and its derivatives in MDR and its mechanism of reversing MDR. Abstract : The MDR of tumors was reversed by anti‐cancer drugscombined with CUR or its derivatives.